Looking into Margaret Atwood’s the Penelopiad: appropriation, parody and class issues - Nunes, Ruan (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2014)
Postmodern writers have often found themselves making use of canonical works in order to expose and subvert ideas. Much has been said about Margaret Atwood’s The Penelopiad, a work which gives Penelope and the hanged maids an opportunity to tell their side of the story – one which went untold in Homer’s The Odyssey. This article offers a brief analysis of how Atwood manages to parody this canonical work in order to reveal the issue of class. Julie Sanders’ study on appropriation (2005) and Linda Hutcheon’s understanding of the parody (2002) will prove fruitful to lead the discussion on these topics.